Gambaran Tingkat Pengetahuan Ibu Tentang Diare Pada Balita Di Kelurahan Baler Bale Agung Kabupaten Jembrana Tahun 2021 - Desak Gede Yenny Apriani, Desak Made Firsia Sastra Putri, Nyoman Sri Widiasari (CV. Pusdikra Mitra Jaya, 2025)
Diarrhea is a disease that causes stool to pass more than 3 times with a liquid consistency that can be accompanied by blood or mucus and is more frequent than normal. Diarrhea is a potential endemic disease of Extraordinary Events (KLB) which is often accompanied by death in Indonesia. Knowing the description of the mother's level of knowledge about diarrhea in toddlers in Baler Bale Agung Village, Jembrana Regency in 2021. This research method uses a descriptive research design. The sampling technique used in this study is a total sampling technique with a sample of 30 respondents. The analysis used in this study is univariate analysis which produces a frequency distribution. This study shows that based on the level of knowledge of respondents about diarrhea, most of the respondents have good knowledge of 18 respondents (60.0%), good knowledge of 10 respondents (33.3%), poor knowledge of 2 respondents (6.7%). The description of Mother's Knowledge Level About Diarrhea in Toddlers shows the results of the mother's level of knowledge which is quite good.